The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2010
DOI: 10.1007/s11367-010-0190-5
|View full text |Cite
|
Sign up to set email alerts
|

Energy-saving policies and low-energy residential buildings: an LCA case study to support decision makers in Piedmont (Italy)

Abstract: Background, aim and scope A low-energy family house recently built in Northern Italy was selected by Regione Piemonte as an outstanding example of resource efficient building. An economic incentive was awarded to cover the extra costs of the thermal insulation, windows and equipment in order to decrease the yearly winter heat requirement from the legal standard of 109 to 10 kW h/m 2 , while existing buildings in the study area typically require 200 kW h/m 2 . As the building was claimed to be sustainable on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(49 citation statements)
references
References 32 publications
0
46
0
Order By: Relevance
“…44,53,96]. In some studies [96] this strategy is mainly intended as a means to support other mitigation strategies, like a wider use of low EE/EC materials, whereas in others policy has a broader reach.…”
Section: Ms5: Policy and Regulations (Governments)mentioning
confidence: 99%
“…44,53,96]. In some studies [96] this strategy is mainly intended as a means to support other mitigation strategies, like a wider use of low EE/EC materials, whereas in others policy has a broader reach.…”
Section: Ms5: Policy and Regulations (Governments)mentioning
confidence: 99%
“…Yet despite this increase, the GWP for all of the CSL's materials is only 10% higher than Junnila's US-based commercial structure, and the embodied energy remains slightly less than Junnila's US structure. Due to previous literature, it was assumed the CSL's materials would have a higher embodied energy when compared to standard buildings [2,3,25]. The next step in this research is to conduct a full LCA of the CSL, which will include the construction, use, and end-of-life phases.…”
Section: Comparison Of Net-zero Building To Standard Buildingsmentioning
confidence: 99%
“…Recent research has found that lower energy houses typically have proportionally higher embodied energy compared to traditional houses, and that while environmental sustainability was improved through reduction in energy use, the embodied energy of the materials, particularly those materials comprising the shell of the structure, actually increases slightly in low-energy buildings [1,[19][20][21][22]25]. Some studies have concluded that embodied energy for conventional buildings accounts for 10%-38% of the total energy in a building's life cycle [2,18,23,26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately 80% of energy use and GHG emissions are generated during the operation stage of buildings (such as heating and cooling, ventilation, lighting, and appliances), whereas only 10% to 20% are from material manufacturing, construction, and demolition [3]. Numerous studies primarily concentrated on developing advanced technologies, policies, and measures to cut down GHG emissions in the operation stage [4][5][6][7] rather than in the construction stage. Guggemos et al [8] pointed out that the environmental impact and GHG emissions from the construction phase cannot be ignored, even if this phase only accounts for 0.4% to 12% of the overwhelming impact from the operation stage.…”
Section: Introductionmentioning
confidence: 99%